E.T.R Restaurant / Muhammad Ihsan Che Azami... [et al.] - Che Azami, Muhammad Ihsan; Shabudin, Khairil Haffifi; Sobri, Mohd. Suhelmiey; Saad, Muhammad Noor Azlan; Abdul Razak, Mohd. Fadzil (2007)
E.T.R Restaurant is a company Traditional and Uniquely Malaysian Food, Catering Service, wireless broadband for internet access, private lounge for private occasion, ala carte breakfast, lunch, dinner and satellite reception and television This business operates in Darulaman Park, Bandar Darulaman, 06000 Jitra, Kedah.